Olive Leaf as a Source of Antibacterial Compounds Active against Antibiotic-Resistant Strains of Campylobacter jejuni and Campylobacter coli - Jose Manuel Silvan; Esperanza Guerrero-Hurtado; Alba Gutierrez-Docio; Marin Prodanov; Adolfo J. Martinez-Rodriguez (MDPI AG, 2022)
Campylobacter spp. are the main cause of bacterial gastroenteritis worldwide, and broiler chicks are the main vector of transmission to humans. The high prevalence of Campylobacter in poultry meat and the increase of antibiotic resistant strains have raised the need to identify new antimicrobial agents. For this reason, the aim of the current study was to evaluate the antibacterial activity of two extracts of olive leaf against antibiotic-resistant Campylobacter strains (C. jejuni and C. coli) isolated from poultry food chain. The extracts of olive leaf (E1 and E2) were markedly different in their chemical compositions. While E1 was composed predominantly of highly hydrophilic compounds such as hydroxytyrosol and hydroxytyrosol glucosides (14,708 mg/100 g), E2 mainly contained moderately hydrophilic compounds, with oleuropein (20,471 mg/100 g) being prevalent. All Campylobacter strains exhibited similar antibiotic profiles, being resistant to ciprofloxacin and tetracycline. E1 showed strong antibacterial activity and reduced bacterial growth from 4.12 to 8.14 log CFU/mL, depending on the strain. Hydroxytyrosol was the main compound responsible, causing the inhibition of growth of Campylobacter strains at low concentrations (0.1-0.25 mg/mL). E2 demonstrated a lower antibacterial effect than E1, reducing growth from 0.52 to 2.49 log CFU/mL. The results of this study suggest that the optimization of the composition of olive-leaf extracts can provide improved treatment results against Campylobacter strains.